THE EFFECT OF USING THINK PAIR SHARE TECHNIQUE TOWARD STUDENTS’ SPEAKING ABILITY AT THE 10TH GRADE OF MAN 3 AGAM - Endang Kurnia; Eliza; Febria Sri Artika; Absharini Kardena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of the Think Pair Share (TPS) technique on students' speaking ability at MAN 3 Agam, where many tenth grade students had difficulty in speaking English. Vocabulary limitations hindered communication during class activities, causing students to prefer using local language which is “Minang language.” Inaccurate pronunciation also caused misunderstandings, making it difficult for them to express ideas spontaneously. This study used quantitative methods with a quasi-experimental research design of nonequivalent control group design. The population of this study were all tenth grade students at MAN 3 Agam, with samples selected by cluster random sampling. Class XE.2 was selected as the experimental group and XE.3 as the control group. The instrument used was an extensive speaking test (monologue), which was validated by content validation and tested for reliability using Inter-rater reliability with Intraclass Correlation Coefficient (ICC) method. Data analysis included normality and homogeneity tests, followed by hypothesis testing using paired sample t-Test and independent sample t-Test. The results of the paired sample t-test in the experimental class showed Sig (2-tailed) <0.05, indicating a significant effect of TPS. The independent sample t-test comparing the two classes also showed Sig (2-tailed) < 0.05, indicating a significant difference between students taught with TPS and those not taught with TPS. The post-test scores showed that the experimental class achieved a higher mean score than the control class, indicating that the speaking ability of the class taught using TPS technique was better than the class not taught using TPS technique.